Molecular epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) among veterinary students and personnel at a veterinary hospital in Malaysia - Erkihun Aklilu; Zunita, Z.; Chen Hui Cheng (ELSEVIER, 2013)
In this study, we report the molecular epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) among veterinary students and personnel in Malaysia. Nasal and oral swabs were collected from 103 veterinary medicine students and 28 personnel from a veterinary hospital. Antibiotic sensitivity test (AST), minimum inhibitory concentration (MIC) test, and PCR amplifications of nucA and mecA gene were performed. Molecular characterization of the isolates was conducted using multilocus sequence typing (MLST), staphylococcal protein A gene (spa) typing, and pulsed-field gel electrophoresis (PFGE). Results from MLST show the presence of the pandemic and widespread MRSA clones, ST5 and ST59. Spa gene typing revealed spa type t267 which has a wide geographical distribution. A new spa type, t5697 was found in this study. Fingerprint analysis by using PFGE show heterogeneity of the isolates. These findings affirm the importance of MRSA in veterinary settings and underscore the need for further extensive research to devise contextual control and prevention strategies.